CYTOCHEMICAL AND DEVELOPMENTAL CHANGES IN MICROBODIES (GLYOXYSOMES) AND RELATED ORGANELLES OF CASTOR BEAN ENDOSPERM - Vigil, Eugene L. (The Rockefeller University Press, 1970)
Structural changes in endosperm cells of germinating castor beans were examined and complemented with a cytochemical analysis of staining with diaminobenzidine (DAB). Deposition of oxidized DAB occurred only in microbodies due to the presence of catalase, and in cell walls associated with peroxidase activity. Seedling development paralleled the disappearance of spherosomes (lipid bodies) and matrix of aleurone grains in endosperm cells. 6 to 7 days after germination, a cross-section through the endosperm contained cells in all stages of development and senescence beginning at the seed coat and progressing inward to the cotyledons. Part of this aging process involved vacuole formation by fusion of aleurone grain membranes. This coincided with an increase in microbodies (glyoxsomes), mitochondria, plastids with an elaborate tubular network, and the formation of a new protein body referred to as a dilated cisterna, which is structurally and biochemically distinct from microbodies although both apparently develop from rough endoplasmic reticulum (ER). In vacuolate cells microbodies are the most numerous organelle and are intimately associated with spherosomes and dilated cisternae. This phenomenon is discussed in relation to the biochemical activities of these organelles. Turnover of microbodies involves sequestration into autophagic vacuoles as intact organelles which still retain catalase activity. Crystalloids present in microbodies develop by condensation of matrix protein and are the principal site of catalase formerly in the matrix.